The relationships between tactical formation, technical-tactical performance, and match outcome in the Ethiopian Bet King Premier League - Chekle, Belayneh; Solomon, Tebibu; Tadesse, Tefera; Shewangizaw, Wondimagegn (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to conduct a comprehensive analysis using a correlational study design to find the relationships between tactical formation, technical-tactical performance, and match outcome in the Ethiopian Bet King Premier League. Out of the seasons 240 matches, 40 matches were taken using a purposive sampling technique. A conceptual model guided the study process and how the study variables relate to one another, illuminating the dynamics that affect success in competitive soccer situations. The study results showed that in the Ethiopian Bet King Premier League, formation does not correlate with either technical-tactical performances such as ball possession and shots or with match outcomes, except the interrelationship among the technical tactical performance parameters and match outcome. However, a significant difference exists among the formations only in possession percentage F (3, 76) = 3.018, p = .035. The study has the implication that investigation of key performance indicators (KPIs) in today’s soccer must go far beyond identifying advanced performance indicators that can reflect the outcome of the game. Thus, for coaching, it implies that what matters the most is not the position we give to each player and the number of players in each position; instead, the complex intricacies of players’ movement, decisions, and positional change among the players could be potential factors for winning/match outcome.